Protection of Internally Displaced Persons in Kenya under the Prevention, Protection and Assistance to Internally Displaced Persons and Affected Communities Act of 2012 : An Appraisal - Juma, Laurence (Comparative and International Law Journal of Southern Africa, 2020)
This article discusses Kenya’s Prevention, Protection and Assistance to Internally Displaced Persons and Affected Communities Act of 2012, which is among the very few national legislations globally that addresses the plight of internally displaced persons. While it records the momentous achievement in creating a viable and legally enforceable legislative framework for the protection of IDPs, the article highlights some of the areas that could be improved for the Act to realise its promise. It notes for example the inchoate manner in which institutions are created and the lack of resources. The article while isolating these challenges also suggests numerous ways in which such challenges can be overcome. It underscores the need for harmonised legal regimes, improvement of data collection and proper monitoring programmes, all which can be achieved and strengthened by a supportive political establishment as well as strategic amendments to various provisions of the Act.